Affluence and Influence : Economic Inequality and Political Power in America - Gilens, Martin (Book collections on Project MUSE., 2012)
Can a country be a democracy if its government only responds to the preferences of the rich? In an ideal democracy, all citizens should have equal influence on government policy--but as this book demonstrates, America's policymakers respond almost exclusively to the preferences of the economically advantaged. Affluence and Influence definitively explores how political inequality in the United States has evolved over the last several decades and how this growing disparity has been shaped by interest groups, parties, and elections. With sharp analysis and an impressive range of.